STUDI TENTANG ANALISIS NILAI-NILAI PANCASILA YANG TERKANDUNG DALAM TATA CARA TRADISI PERKAWINAN SUKU BATAK TOBA DI DURI KECAMATAN MANDAU KABUPATEN BENGKALIS - Claudya Octavianti; Hambali Hambali; Ahmad Eddison (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the Pancasila values contained in the marriage tradition of the Batak Toba tribe in Duri, Mandau District, Bengkalis Regency. . The formulation of the problem in this study is how the Pancasila values contained in the tradition of the Batak Toba marriage in Duri, Mandau District, Bengkalis Regency. The aim is to find out how the Pancasila values are contained in the tradition of the Batak Toba marriage in Duri, Mandau District, Bengkalis Regency. In July 2020 to August 2020. This research is a qualitative descriptive study. Respondents in this study were the Head of the Toba Batak Customs and communities. Using data collection techniques: observation, interviews, questionnaires, literature study, and documentation. Data analysis techniques using data analysis techniques: data collection, classifying alternative answers to respondents. The results of this study determine the percentage of alternative answers to respondents using the formula P = f / n x 100% presenting in tabular form, and drawing conclusions. Based on the results of the research, it shows that there are Pancasila values from the five precepts, namely, one supreme deity, fair and civilized humanity, Indonesian unity, democracy led by wisdom in representative deliberation and social justice for all Indonesian people. This is indicated by the recapitulation of the fourth and fifth precepts which are the highest number of respondents answered and the third principle is the lowest number of principles answered by the respondents, the values of Pancasila contained in the tradition of the Batak Toba marriage in Duri, Mandau District, Bengkalis Regency.Key Words: Analysis Of The Value Of Pancasila, The Tradition Of Marriage, The Batak Toba